Evaluación del plaguicida orgánico a base de saponina de quinua (chenopodium quinoa) para el control de gusano blanco (premnotrypes vorax) en condiciones de laboratorio. - Llundo Agualongo, Monica Isabel (2024)
The white worm (Premnotrypes vorax) is one of the pests that cause high production losses mainly in the cultivation of potatoes and cucurbits, affecting farmers, which has forced them to look for alternatives based on plant extracts to control the pest and Avoid frequent applications of chemical products that may cause chemical resistance. The present research was carried out in the laboratories of the Technical University of Cotopaxi and the Technical University of Ambato with the objective of evaluating the effect of the organic extract based on quinoa saponin (Chenopodium quinoa) on the white worm with six concentrations in v/ v of 10%, 20%, 30%, 40%, 50% and 60% and the control 0%, the presence of metabolites of the plant extract was qualitatively and quantitatively carried out through screening, obtaining as a result the compounds with the highest presence of alkaloids, saponins , tannins or polyphenols and triterpenes, a Completely Randomized Design (DCA) was carried out with six treatments including the control with three repetitions, each treatment contained five individuals (white worms) placed in plastic containers where the plant extract was applied in one hour with an interval of 20 minutes through observation, the dead individuals were counted after application, the 60% concentration at 20 minutes obtained an average of 3 dead white worms, while at 40 minutes an average of 4 and Finally, after 60 minutes an average of 5 dead white worms.